1982
DOI: 10.3758/bf03327004
|View full text |Cite
|
Sign up to set email alerts
|

The gustatory neocortex of the rat

Abstract: Research findings related to the functional significance of the gustatory neocortical system of the rat are reviewed and interpreted. Studies of gustatory neocortex (GN) involvement in taste-related cognitive processes are emphasized after briefly reviewing GN anatomy and physiology. Evidence is presented supporting the conclusion that the GN contributes relatively little to fundamental taste reactivity, but is deeply involved in cognitive (learning and memorial) taste processes; that is, "reactive salience" t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
110
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 176 publications
10
110
1
1
Order By: Relevance
“…In fact, widespread damage to areas consistent with this location have been reported in studies using ablation, electrolytic, and even neurotoxic approaches in studies indicating a role for GC in CTA (e.g., refs. 2,18,21,22,25,27,30,36,37). This, coupled with the fact that previous studies (24,38) showed that neither damage to AI just caudal to GC nor to an area even more posterior in insular cortex than the hot spot identified here affected CTA, highlights the strong possibility that discrepancies across studies critically hinge upon the involvement of a specific area (or areas) of this cortical region.…”
Section: Discussionsupporting
confidence: 55%
“…In fact, widespread damage to areas consistent with this location have been reported in studies using ablation, electrolytic, and even neurotoxic approaches in studies indicating a role for GC in CTA (e.g., refs. 2,18,21,22,25,27,30,36,37). This, coupled with the fact that previous studies (24,38) showed that neither damage to AI just caudal to GC nor to an area even more posterior in insular cortex than the hot spot identified here affected CTA, highlights the strong possibility that discrepancies across studies critically hinge upon the involvement of a specific area (or areas) of this cortical region.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, because rats in group Devalue would respond to sweet with aversive responses, by associatively activating a perception of sweetness, the tone would provoke aversive responses in that group. Notably, although GC is not critical to basic functions of taste detection (e.g., Dunn and Everitt 1988), it has been shown to be importantly involved in many aspects of higher-level processing of taste memories (e.g., Braun et al 1982;Rosenblum et al 1995Rosenblum et al , 1997. Most relevant to the present study, Kiefer and Orr (1992) found that rats with GC lesions failed to replace appetitive taste-reactivity responses to a sweet flavor with aversive responses after flavor-illness pairings, even under circumstances under which those lesioned rats successfully learned to suppress overall consumption of that flavor.…”
Section: Discussionmentioning
confidence: 99%
“…Although this could readily explain a lesion-induced overconsumption of saccharin on the first pre-exposure trial (lower concentrations of saccharin evoke less neophobia than do higher concentrations), it would not mean that ICX-Novel rats would acquire the taste aversion as slowly as the ICX-Familiar subjects [latent inhibition occurs even with low concentrations of saccharin; for example, De La Casa & Lubow (2002) used 0.04% saccharin]. Finally, it might be noted that there is empirical evidence that IC lesions do not disrupt basic taste perception (Braun et al 1982).…”
Section: Discussionmentioning
confidence: 99%